A Molecular Dynamics Simulation Study on Separation Selectivity of CO2/CH4 Mixture in Mesoporous Carbons. (January 2016) - Trinh, Thuat T.; Tran, Khanh-Quang; Bach, Quang-Vu; Trinh, Dao Q.
Abstract: The effect of surface charged defects in carbon mesoporous materials on adsorption selectivity for a CO2 /CH4 gas mixture relevant to natural gas was studied by means of classical molecular dynamics (MD) simulation. The mole fraction of CO2 was 0.1, T = 300K and the partial pressure of CO2 was up to 40 bars. A graphite slit pore of 3.0 nm was taken as a model for mesoporous carbon. The localized charged defects within an electroneutral pore surface were found to increase the CO2 /CH4 separation selectivity. In addition, such surface charges interact with CO2 molecules only. The selectivity reduces with increasing pressures. Our model with a defect charge of 0.2 electron/atom can reproduce the selectivity CO2 /CH4 of the experimental data reported in the literature. A perfect charge graphite model underestimates the adsorption selectivity of CO2 /CH4 . The results show that a very high selectivity around 25 can be achieved with a charged defect of 0.45 electron/atom. This suggests that controlling the charged defects on surface of carbon mesoporous can be used to enhance the CO2 /CH4 separation for natural gas.